CMV infection among HIV / AIDS patients in Iraq - Orer, Ali R.; Alizi, Sana M.H.; Al-Diwan, Jawad K. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: The aim of the study was to determine the prevalence of CMV infection among HIV / AIDS patients in relation to disease progression, and to study the mortality during the period of the study. Patients and Methods: The study included 155 HIV/AIDS patients (148 HIV- infected and seven AIDS patients) and 122 apparently "healthy" controls. CMV (IgG and 1gM) antibodies were determined by ELISA. The patients were followed up for a period of nine months, and retested frequently for development of active CMV infection. Results: The prevalence of CMV (IgG) antibodies in the HIV/AIDS patients was 100%. A significant higher prevalence of CMV (IgM) among AIDS patients (42.9°/6) than among HIV infected patients (0.0%) and "healthy" controls (0.8%). No deaths were reported among asymptomatic HIV infected patients while the mortality among AIDS patients was (42.9%). Only one patient (7.7%) out of 13 asymptomatic HIV infected developed active CMV infection 10 years later by testing for CMV (IgM) in 1991 and 2001. Conclusion: Demonstration of active CMV is of prognostic value in detection of development of AIDS and survival of patients.